Asuhan Keperawatan pada Nn. M dengan Gangguan Sistem Endokrin: Post Op Isthmolobektomi dengan Indikasi Struma Nodusa Non Toksik di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Icha Hayuning Wulan; Ahmad Zakiudin; Yusriani Saleh Baso (Jurnal Anestesi, 2024)
Non-toxic goiter nodusa is an enlargement of the thyroid gland in which one or more nodules are clinically detected without hyperthyroidism (Sari et al., 2021). The purpose of this writing is to find outand provide nursing care to Ms. M with endocrine system disorders: post op isthmolobectomy with indications of non-toxic nodal goiter in mawar ward 2 RSUD dr. Soeselo Tegal Regency in accordance with nursing standards. The method used is a descriptive method in the form of interviews, observation, documentation studies, library and literature studies. From the case review, it was found that the patient’s main comlaint was pain in the surgical wound on the left side to the neck, P:pain worsened when mobilizing, speaking and swallowing, Q: pain like being cut, R: pain on the left side of the neck, S: scale 4, T: disappears. There were three diagnoses found, namely acute pain, knowledge deficit and risk of infection. Intervetions are prepared based on the theory of SDKI, SLKI and SIKI as well as on the client’s condition and can be implemented.